Analysis of Human Resource Management System Using Data Flow Diagram - Bograin, Elham (Libyan Journal for Engineering Research, 2017)
This paper search a system analysis methodology for Human Resource Management System (HRMS) using Data Flow Diagrams (DFDs). Several steps will be required to accomplish this work. The first step includes the determination of system boundaries, processes, and data entities. In the second steps, system sources and destinations will be presented on context diagram (level 0). Then data links, processes, and sub-processes will also be presented on data flow diagrams of level 1 and level 2 respectively. Finally, a complete logical model representing a system analysis of HRMS will be documented using DFDs. The use of DFDs lead directly into physical design, with processes suggesting programs and procedures, data flows suggesting composites, and data stores suggesting data entities; files; and database.